IDEOLOGI DALAM PIDATO KENEGARAAN PRESIDEN SOEKARNO PADA KTT NON BLOK DI KAIRO (ANALISIS WACANA KRITIS ) - Intan Rawit Sapanti (JURNAL KONFIKS, 2018)
critical in Soekarno's state speech entitled Period of Confrontation: Speech of President Sukarno at the Conference of the Two Non-Aligned Nations in Cairo? As well as any ideologies that accompany it. This research is a descriptive study of Bung Karno's speech delivered in a fiery manner, always filled with messages of national ideology. Through the discourse in each of his speeches, President Soekarno tried to voice resistance to colonialism and arouse fighting spirit to rise. In this study, it will be investigated further with qualitative discourse analysis. The data collection method used in this study is the referral method. The data used in this research is written discourse in the speech delivered by President Sukarno at the Non-Aligned Summit in Cairo. The results of this study through analysis of the structure of micro discourse through 1) lexicon, 2) stylistics, 3) syntax can be concluded that there are several ideologies that Bung Karno wants to convey through his speech. One of them is about real independence. The real independence in question is freedom to carry out political, economic and social affairs in line with the national conceptions of each country, so that there is no interference from other countries. While the other ideology that President Soekarno wanted to carry out was to call on countries in the world to fight imperialism, colonialism, neo-imperialism and neo-imperialism without fear.